Biosynthesis of A6'7-anhydroerythromycin via enoyl reductase inhibition by isonicotinic hydrazide (INH) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1999)
Isonicotinic hydrazide (INH) was added to a fermentation of mutant of Saccharopolyspora erythraea ATCC 11912 to inhibit the activity of 2,4,6,8-tetramethyI-7,9-dihydroxy-2-en-5-on-undecyl-ACP enoyl reductase, an enzyme which catalyses enoyl reduction process of an intermediate in the erythronolide biosynthesis, and produce A"3-anhydroerythromycin derivative. The. optimum INH additional concentration of above 0.1% was able to inhibit the enzyme activity, and produce A6â¢7-anhydroerythromycin derivative as shown by FT-infrared spectrophotometric analysis of the product after its purification using thin layer chromatography.